Unraveling the complexity of fintech adoption: A multidimensional analysis of sustained digital wallet usage by Generation Z in Greater Jakarta - Anton Hindardjo; Aekram Faisal; Eri Marlapa; Sri Marti Pramudena; Khairul Nizam Mahmud (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study investigates the factors influencing Generation Z's intention to reuse digital wallets in the Greater Jakarta area, focusing on perceived ease of use, brand image, e-service quality, and the mediating role of trust. The research employed a quantitative approach using survey methods, with data collected from 230 Generation Z respondents who have been active digital wallet users for at least one year. Structural equation modeling was used to analyze the relationships between variables. The results reveal that perceived ease of use and brand image have positive effects on reuse intention, while e-service quality indirectly influences reuse intention through trust. Trust plays a significant mediating role in the relationships between brand image and e-service quality with reuse intention. However, contrary to previous studies, perceived ease of use did not significantly affect trust, nor did trust mediate the relationship between perceived ease of use and reuse intention. These findings highlight the importance of building a strong brand image and providing high-quality electronic services to enhance trust and promote continuous use of digital wallets among urban Indonesian youth. The study contributes to the understanding of digital wallet adoption and usage dynamics in emerging markets, offering valuable insights for service providers targeting young urban consumers in Indonesia. It also opens avenues for future research on the evolving perceptions of digital financial technologies among Generation Z users.